Degrading Vibrio cholerae Biofilms with Bacteriophage and potential combined effect of phage and antibiotic on biofilms - Hasan, Md Rockybul (Brac University, 2023)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2022.